Studi Deskriptif : Kepatuhan Minum Obat pada Anggota Polri yang Menjalani Pengobatan di Biddokkes Polda Papua - Mega Agustiani Harsi; Iskim Lutfiana; Abrori Abrori (Jurnal Siti Rufaidah, 2025)
. Indonesian National Police (Polri) members are state officials who play a strategic role in maintaining security, order, law enforcement, and providing protection, care, and service to the community. As civil servants of the Indonesian National Police (POLRI), Polri members are required to be in excellent health to optimally carry out their duties and responsibilities. One of the challenges faced is adherence to medication, especially for Polri members undergoing medical treatment. Medication adherence is a crucial factor in successful treatment, and one determinant that can influence adherence is family support. This study aims to describe the relationship between medication adherence and family support among Polri members undergoing treatment at the Papua Regional Police Medical and Health Unit. The research method used is descriptive quantitative, namely research that focuses on describing social phenomena through numerical data obtained from measurements and analyzed statistically. This study does not aim to test hypotheses, but rather to explain the characteristics and trends that emerge from the data obtained. The results show that of the 24 respondents with high medication adherence, 17 (70.8%) received high family support. These findings confirm that family support significantly contributes to the level of compliance of Indonesian National Police (Polri) members with their medication. Therefore, the role of the family needs to be given greater attention in efforts to improve the success of treatment, particularly among Polri members. The study concluded that the better the family support received, the higher the level of medication compliance, which ultimately positively impacts the health of Polri members.